KEARIFAN LOKAL ORANG BUGIS-MAKASSAR DALAM UPAYA MITIGASI PANDEMI COVID 19 PADA MASYARAKAT KOTA MAKASSAR - Burhan Kadir Kadir; Icha Musywirah Hamka (Universitas Hasanuddin, 2022)
The covid-19 virus spreads rapidly through transmission, making it difficult for even developed countries to control. Indonesia is experiencing difficulties mitigating the Covid-19 pandemic due to its large population and remote location. The purpose of this article is to examine the local wisdom in the Bugis-Makassar community in Makassar, which helps prevent the transmission of covid-19. Local wisdom is a way of understanding life and knowledge and combining it with strategies that the local community uses to solve different problems and meet their needs.As a consequence of the ancestral heritage of the Bugis-Makassar community related to the environment, they have accumulated a great deal of local wisdom about diseases prevention and treatment. By applying local wisdom in the community, each individual becomes accustomed to and forms his character by being limited and regulated by local wisdom.